Measuring brain synaptic vesicle protein 2A with positron emission tomography and [18F]UCB‐H. Issue 4 (29th August 2017) - Bahri, Mohamed Ali; Plenevaux, Alain; Aerts, Joël; Bastin, Christine; Becker, Guillaume; Mercier, Joël; Valade, Anne; Buchanan, Tim; Mestdagh, Nathalie; Ledoux, Didier; Seret, Alain; Luxen, André; et al.
Abstract: Introduction: Brain distribution of synaptic vesicle protein 2A was measured with fluorine‐18 UCB‐H ([ 18 F]UCB‐H) and positron emission tomography (PET). Methods: Images of synaptic density were acquired in healthy volunteers (two young participants and two seniors). Input function was measured by arterial blood sampling (arterial input function) and derived from PET images using carotid activity (image‐derived input function). Logan graphical analysis was used to estimate regional synaptic vesicle protein 2A distribution volume. Results: [ 18 F]UCB‐H uptake was ubiquitous in cortical and subcortical gray matter. Arterial input function and image‐derived input function provided regional distribution volume with a high linear relationship. Discussion: The cerebral distribution of [ 18 F]UCB‐H is similar to that recently observed with carbon‐11 UCB‐J ([ 11 C]UCB‐J). An accurate [ 18 F]UCB‐H quantification can be performed without invasive arterial blood sampling when no suitable reference region is available, using dynamic PET carotid activity. Brain synaptic density can be studied in vivo in normal and pathological aging. Highlights: Measuring brain synaptic density is possible with radiotracers of synaptic vesicle protein 2A. Brain distribution of [ 18 F]UCB‐H can be modeled using positron emission tomography carotid activity. Brain synapses can be measured with positron emission tomography in early stages of Alzheimer's disease.